2016
DOI: 10.1167/iovs.15-17693
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Prostaglandin FP and EP2 Receptors Differently Modulates Myofibroblast Transition in a Model of Adult Primary Human Trabecular Meshwork Cells

Abstract: PURPOSE. Prostaglandin F2a analogues are the first-line medication for the treatment of ocular hypertension (OHT), and prostanoid EP2 receptor agonists are under clinical development for this indication. The goal of this study was to investigate the effects of F prostanoid (FP) and EP2 receptor activation on the myofibroblast transition of primary trabecular meshwork (TM) cells, which could be a causal mechanism of TM dysfunction in glaucoma.METHODS. Human primary TM cells were treated with either latanoprost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Fibrosis also involves an accumulation of ECM, which was also observed in the glaucomatous TM . The hypothesis of an involvement of fibrotic processes in POAG‐related modulations of TM that could be mediated by increased levels of transforming growth factor β2 (TGFβ2) in the aqueous humour has already been discussed . The MCODE cluster of AAbs potentially reflects POAG‐specific alterations of the PDGFRB pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrosis also involves an accumulation of ECM, which was also observed in the glaucomatous TM . The hypothesis of an involvement of fibrotic processes in POAG‐related modulations of TM that could be mediated by increased levels of transforming growth factor β2 (TGFβ2) in the aqueous humour has already been discussed . The MCODE cluster of AAbs potentially reflects POAG‐specific alterations of the PDGFRB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…48 The hypothesis of an involvement of fibrotic processes in POAG-related modulations of TM that could be mediated by increased levels of transforming growth factor b2 (TGFb2) in the aqueous humour has already been discussed. 49,50 The MCODE cluster of AAbs potentially reflects POAG-specific alterations of the PDGFRB pathway. However, a causative or synergetic effect of these AAbs in mediating autoimmune-driven fibrosis in glaucomatous TM cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In studying the cellular actions of FP receptor and EP 2 receptor agonists in h‐TM cells, Kalouche et al . () showed that latanoprost‐free acid prevented collagen accumulation and contracted TM cells, both processes being antagonized by AL‐8810. In contrast, the EP 2 receptor agonist, butaprost, relaxed TM cells and reduced collagen deposition induced by TGFβ2 .…”
Section: Al‐8810 Antagonizes In Vitro Ocular Actions Of Fp Receptor Amentioning
confidence: 98%
“…Relaxation of TM cells as a result of a reduction of actin stress fibers and vinculin localization at focal adhesions was observed using such analogs [171]. Interest is increasing in the development of EP 2 and EP 4 receptor agonists for the treatment of POAG, with one such EP 2 agonist having been shown to reduce IOP by increasing both unconventional and conventional flow, facilitated by the relaxation of SC and by decrease in contractility and collagen deposition at the TM [172][173][174]. These effects are similar to those of traditional FP receptor agonists, however these, in contrast, may increase TM contractility.…”
Section: New Classes Of Drugmentioning
confidence: 99%